2008
DOI: 10.3317/jraas.2008.002
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the angiotensin-converting enzyme gene (I/D) polymorphism and diabetic nephropathy in Tunisian type 2 diabetic patients

Abstract: Paper AbstractObjective. The aim of the present study was to investigate whether the angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism is associated with diabetic nephropathy and type 2 diabetes in the Tunisian population. Design. A case-control study was conducted among 141 unrelated type 2 diabetic patients with (90 patients) or without nephropathy (51 patients) and 103 non-diabetic controls with normal fasting blood glucose. Genotyping was performed using a nested polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
7
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 45 publications
9
39
7
1
Order By: Relevance
“…In contrast, among Caucasians French, Turkish and Tunisian populations the ACE I/D polymorphism was not a marker for DN and renal prognosis of patients with T2DM (6,16,17,28). Also, among Iranians with Kurdish ethnic background ACE I/D polymorphism was not associated with the risk of microalbuminuria (10).…”
Section: Ace I/d Polymorphism: Onset and Progression Of Diabetic Nephmentioning
confidence: 75%
See 3 more Smart Citations
“…In contrast, among Caucasians French, Turkish and Tunisian populations the ACE I/D polymorphism was not a marker for DN and renal prognosis of patients with T2DM (6,16,17,28). Also, among Iranians with Kurdish ethnic background ACE I/D polymorphism was not associated with the risk of microalbuminuria (10).…”
Section: Ace I/d Polymorphism: Onset and Progression Of Diabetic Nephmentioning
confidence: 75%
“…The frequency of ACE alleles varies in different ethnic groups and might contribute to the conflicting results related to the role of ACE (I/D) polymorphism in diabetic nephropathy (5,6).…”
Section: Angiotensin Converting Enzyme (Ace) Gene Polymorphismmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same line, several studies in different population have reported that a strong relationship between the ACE DD genotype and the risk for diabetic nephropathy was reported in Malaysian [18], British Caucasian [19], Bahraini [20], Japanese [21], Korean [22], and Americans [14] populations. However, information from other studies in Chinese [23], German [24], Danish [25], Turkish [26], and Tunisian [27] populations were unsuccessful to prove this association. There were conflicting results in Iranian population regarding the association of ACE polymorphism; Nikzamir [28] demonstrated strong relation between the homozygous DD and nephropathy while Rahimi [29] showed no significant association.…”
Section: Discussionmentioning
confidence: 99%